Impact of renal function on mean platelet volume and its relationship with coronary artery disease: A single-centre cohort study. Issue 141 (May 2016) - Verdoia, Monica; Barbieri, Lucia; Schaffer, Alon; Bellomo, Giorgio; Marino, Paolo; De Luca, Giuseppe; ,
Abstract: Background: Mean platelet volume (MPV) has been proposed as a marker of platelet reactivity and cardiovascular disease. Chronic kidney disease (CKD) significantly favors the occurrence of cardiovascular events, by increasing the circulating levels of a wide spectrum of pro-oxidant and pro-thrombotic mediators. However, opposite alterations of platelet function, both enhanced aggregability and increased bleeding diathesis have been reported in these patients, with contrasting results on the effects of renal function on MPV and coronary artery disease, that were assessed in present study. Methods: In patients undergoing coronary angiography, MPV and renal function (serum creatinine and estimated Glomerular Filtration Rate, eGFR, by MDRD formula) were assessed at admission. Coronary artery disease (CAD) was defined as a stenosis > 50% in at least 1 coronary vessel, while severe CAD as left main or trivessel disease. Results: Among 3712 patients, 1044 (28.1%) had chronic kidney disease. CKD was related with age, female gender, diabetes and glycemic control, history of myocardial infarction, cerebrovascular accidents, coronary artery bypass grafting and left ventricular dysfunction or arrhythmias as indication to angiography, therapy with angiotensin-receptor blockers, nitrates, diuretics and calcium-antagonists, but lower rate of smoking, lower fibrinogen levels, haemoglobin, total and HDL cholesterol ( p < 0.001, respectively). CKD patients displayed increased severity and complexity of CAD ( p < 0.001) and significantly larger platelet volume ( p < 0.001), with CKD resulting as independent predictor of MPV above the median (≥ 10.85 fl; Adjusted OR[95%CI] = 1.56[1.23, 1.99], p = 0.002). Moreover, in the 1044 patients with renal failure, higher platelet volume (above the median value; ≥ 10.85 fl) was associated with age ( p = 0.05), haemoglobin levels and platelet count ( p < 0.001), but not to a higher prevalence or extent of coronary artery disease (CAD: adjusted OR[95%CI] = 0.80[0.58–1.09], p = 0.16; severe CAD, adjusted OR[95%CI] = 1.07[0.81–1.41], p = 0.65). Conclusions: Higher values of MPV are observed among patients with chronic kidney disease, inversely relating to eGFR. However, larger platelet size does not contribute to explain the increased severity of coronary artery disease observed among these patients. Highlights: Chronic kidney disease (CKD) represents a condition with a very high cardiovascular and thrombotic risk Mean platelet volume (MPV) has been previously proposed as a cheap and easy to obtain predictor of cardiovascular events We evaluated the impact of CKD on MPV and their potential interaction in explaining the occurrence of CAD in these patients Among 3712 patients, more than 28 the > 28% of patients with CKD displayed higher values of MPV inversely relating to eGFR. Larger platelet size did not contribute to explain the severity of coronary artery disease observed among these patients